Effects of destruxin A on Rhipicephalus (Boophilus) microplus ticks (Acari: Ixodidae) - Gôlo,Patrícia Silva (2011)
This study evaluated the effects of destruxin A on Rhipicephalus (Boophilus) microplus females, since this toxin is one of the likely causes of high mortality induced by the entomopathogenic fungus Metarhizium anisopliae in arthropods. Ticks were immersed or inoculated with different concentrations of destruxin A. Despite the doses applied, there were no deaths or significant alterations in oviposition between the groups treated with destruxin A and the control groups. No other external effect caused by destruxin, such as tetanic paralysis, was observed in these engorged female ticks after the treatment.